Seizure in cerebral venous and sinus thrombosis. Issue 3 (8th June 2018) - Mehvari Habibabadi, Jafar; Saadatnia, Mohammad; Tabrizi, Nasim
Summary: Many conflicting issues exist about seizure in the setting of cerebral venous and sinus thrombosis (CVST). In this article we aimed to address the existing data regarding incidence, characteristics, predictors, treatment, and prognosis of acute and late seizures in patients with CVST and to prepare more practical information for clinicians. PubMed, Embase, Web of science and Cochrane databases were searched within 1966–2016 using relevant keywords. A total of 63 papers met the inclusion criteria. Seizures are classified as acute symptomatic seizures (ASS; first 14 days) and post‐CVST epilepsy (PCE; after 14 days). The incidence had been reported in a wide range of 6.9–76% for ASS and 4–16% for PCE. Focal and generalized seizures were observed with different predominance. ASS commonly occurred in patients with loss of consciousness, focal neurological deficits, supratentorial lesions and thrombosis in superior sagittal sinus, straight sinus, and cortical veins. PCE had been predisposed by occurrence of ASS, motor deficit, and supratentorial lesions, particularly hemorrhage. Most experts believe that primary prophylaxis with antiepileptic drugs in the acute phase is not indicated. However, the initiation of prophylaxis after the first seizure in patients with supratentorial lesions or focal neurological deficit should be recommended. The quality of current evidence is low and most conclusions are based on expert opinions. More accurate reports of seizure semiology, detailed antiepileptic treatment plans, and outcomes are necessary to answer the existing questions.